INOVASI “REMINDER’’ SEBAGAI STRATEGI INTERVENSI KEPERAWATAN KOMUNITAS DALAM MENGATASI MASALAH RESILIENSI PADA MAHASISWA SEMESTER PERTAMA PRODI SARJANA KEPERAWATAN ANGKATAN 2018 UNDIP SEMARANG - Janah, Esti Nur; Dewi, Nur Setiawati (Journal of Bionursing, 2020)
Background: The first-year students have higher stress levels when compared with other students for the first year students will be faced with the pressing events such as the conflict relationship with his parents, girlfriend, and friends and low academic achievement, financial issues and adjustment to the new social environment. The purpose of this study is to provide community nursing intervention strategies through innovation program REMINDER (resilience, Mindfulness, aerobic) in the first semester students of nursing undergraduate study program in addressing the risk of stress. Methods: Community nursing care in college setting with a quasi-experimental design approach became the method in this study. The population in this study is the first semester students of Diponegoro University nursing undergraduate study program with a total sample of 68 students. Results: The level of stress experienced by students increases. Coping kind used tend to be similar both before and after the intervention. Resilience of students increased to 100% high resilience. Life satisfaction is almost the same between before and after the intervention.Conclusion: REMINDER innovation program failed to give effect to overcome the psychological problems of students in the first year because do not match the frequency of the planned targets. Educational institutions are expected to carry out a review and evaluation of non-academic assignment of the student organization because it was discovered several incidents of pain on freshmen result in the assignment of student organizations.